Correlation between Iron Parameters and Platelet Parameters in Iron Deficiency Anemia - Chalise, Sanat; Acharya, Nishant; Pradhan, Sailesh B (Journal of Institute of Medicine Nepal, 2019)
Introduction Iron deficiency anemia is the most common type of anemia and is diagnosed by iron studies. Reactive thrombocytosis is usually seen in iron deficiency anemia. The objectives of the study is to correlate between iron parameters and platelet parameters in patient with iron deficiency anemia. Methods This was a cross-sectional study done in Department of Pathology at Kathmandu Medical College, Sinamangal between December 2018 to May 2019. Blood samples of 81 iron deficiency anemia patients were analysed to determine iron parameters and platelet parameters. SPSS version 20 was used to analyse the data. Results Thrombocytosis was seen in 62 (76.5%) patient with iron deficiency anemia. Platelet count was negatively correlated with serum iron, percentage saturation and platelet distribution width (p˂0.001, for all) while positive correlation was obtained between platelet count and plateletcrit (p<0.05). Plateletcrit showed negative correlation with serum iron (p˂0.001) and platelet distribution width (p<0.05) while positive correlation was obtained with mean platelet volume, total iron binding capacity and platelet (p<0.05, for all). There was negative correlation between mean platelet volume and platelet count (p<0.001). Positive correlation was obtained between mean platelet volume and plateletcrit (p<0.05). Correlation was not found between mean platelet volume and iron parameters (p>0.05). Platelet distribution width showed negative correlation with total iron binding capacity, platelet (p˂0.001, for both), plateletcrit (p<0.05). Conclusion Thrombocytosis is more commonly observed as compared to thrombocytopenia in patient with iron deficiency anemia. Serum iron and percentage saturation are the most important parameters affecting the platelet count.